A Comparative Analysis of Financial Performance: Islamic Banks vs. Digital Islamic Banks (2021–2025) - Laila Agustina; Clarashinta Canggih (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
The rapid acceleration of digitalization in Indonesia’s financial sector has transformed banking business models, particularly within Islamic banking institutions. However, limited empirical evidence exists regarding the comparative financial performance of Islamic digital banks and conventional Islamic banks, creating a significant research gap in evaluating the effectiveness of digital transformation. This study aims to analyze and compare the financial performance of Islamic banks and Islamic digital banks in Indonesia during the 2021–2025 period. Employing a quantitative comparative approach, the research examines key financial indicators, including Non-Performing Financing (NPF), Financing to Deposit Ratio (FDR), and Net Profit Margin (NPM), to assess differences in financial stability, liquidity, and profitability. The findings reveal notable differences in several financial ratios between the two banking models, indicating that digital transformation has substantially influenced operational efficiency and profit generation. Islamic digital banks demonstrate relatively stronger adaptability in selected financial performance indicators. This study contributes to the growing discourse on Islamic digital finance and provides strategic insights for policymakers and banking institutions in developing sustainable digital-based Islamic banking systems